Journalists and society - Keeble, Richard (Henry Stewart Talks, 2011)
Overview of journalisms: newspapers, magazines, broadcast journalism, online, news agencies, Alternative media, Theories on the functions of journalism: telling stories, gossip, providing facts, challenging authority, entertaining and educating, setting the agenda, promoting dominant values, promoting cynicism and disrespect, The internet challenge, The radical redefinition of journalism